PYTHON PROGRAMMING LANGUAGE AND ITS FEATURES - Jurayev Sherali Umarjonovich (American Journals, 2023)
Application of automated elements of information system and information technologies and creation of new information technologies based on automation is one of the main tasks of designers of automation systems. In order to create automated systems, first of all, it is important to build an infological or discrete model of the problem object. Depending on the object of the problem, it is necessary to choose based on which algorithm languages should be created, informational or discrete model.
Keywords: Electronic computing machines, information technology, algorithm, Object Pascal, PYTHON, Java, computer.